2019
DOI: 10.1159/000496210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Silver Penetration and Distribution in Carious Lesions of Deciduous Teeth Treated with Silver Diamine Fluoride

Abstract: The aim of this study was to determine the effects of 38% silver diamine fluoride (SDF) on carious lesions of human deciduous teeth. Ten extracted deciduous incisors with caries were collected and treated with SDF. After the treatment, the teeth were sectioned through the center of the carious lesion. The extent of sliver precipitation was examined using quantitative backscattered electron scanning electron microscopy (qBSE-SEM), energy-dispersive X-ray spectroscopy (EDX), and micro-computed tomography (micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 21 publications
9
35
0
Order By: Relevance
“…The presence of chlorine after SDF application, as demonstrated in groups 3 to 6, has also been demonstrated in a previous study [38]; possible explanations for this include the presence of chlorine in the product used, or contamination of the dentinal tubules by chloramine in which the tooth had been stored.…”
Section: Fig 1 E-sem Images (×2000)supporting
confidence: 76%
See 1 more Smart Citation
“…The presence of chlorine after SDF application, as demonstrated in groups 3 to 6, has also been demonstrated in a previous study [38]; possible explanations for this include the presence of chlorine in the product used, or contamination of the dentinal tubules by chloramine in which the tooth had been stored.…”
Section: Fig 1 E-sem Images (×2000)supporting
confidence: 76%
“…The present study did not examine the penetration depth of silver compounds into dentinal tubules. Previous studies of carious dentin have demonstrated a high standard deviation of the penetration depth [38,39]. This can be explained by variations in patient physiological parameters such as age and the type of dentine, resulting in a range of tubule diameters or orientations, depending on the area of the tooth examined.…”
Section: Fig 1 E-sem Images (×2000)mentioning
confidence: 99%
“…This finding is corroborated by histological studies, which showed that carious deciduous dentin treated with 38% SDF exhibited hypermineralization of the intertubular dentin [58], with a higher content of calcium and phosphorus [59] and a few blocked tubules [58]. Beneath that hypermineralized region, the tubules had characteristics of normality.…”
Section: How Is the Deciduous Pulp Reaction To The Sdf Application?mentioning
confidence: 62%
“…Many respondents said that they would require more information or research evidence on the safety of SDF before agreeing to have their child undergo such treatment. Although there is increasing evidence of the effectiveness and safety of SDF as a minimally invasive treatment to arrest ECC 13,36,37 and examples of successful intervention with such products in Indigenous children, 38 parents in this study nonetheless wanted more practical information and evidence in order to make informed choices on SDF. One study concluded that pediatric dentists' confidence in using SDF was correlated with how much knowledge they had of its efficacy.…”
Section: Discussionmentioning
confidence: 99%